Pathogenesis of Major Depression by Stress Induced Hyperactivity of Hypothalmic-pituitary Adrenal Axis Mediated by Dysregulations of Neurotransmitter, Innate Immune Systems and Altered Brain micro RNA Expressions - Basak, Ashim K.; Chatterjee, Tridip (Current Psychiatry Reviews, 2017)
Background: Major depression is a serious mental disorder and an important social problem in which cognitive functions of the patients are substantially deteriorated. Depression is also commonly associated with suicides. Stress induced hyperactivity of the hypothalamic-pituitaryadrenal axis is thought to be an important contributory factor for the development of this psychiatric disease. Objective: The aim of the article is to address the possible mechanisms by which chronic stresses stimulate the hypothalamic-pituitary-adrenal axis that in turn affect the other systems underpinning the pathogenesis of depression. Method: A total of 126 research and review articles were surveyed to elucidate the mechanisms by which stress induced elevated glucocorticoid level causes widespread damages in the brain that predispose to depression. Results: It is evident that chronic stresses induce hyperactivity of the hypothalamic-pituitary-adrenal axis that in turn increases the glucocorticoid level in circulation. Increased glucocorticoid level may activate glutamate-induced excitotoxicity that in turn makes damages to the monoamine neurotransmitter systems. Excessive glucocorticoid also induces the release of inflammatory cytokines in the brain. Furthermore, the steroid can also dysregulate the microRNA expressions in the brain. All these effects together may aggravate the state of depression. Conclusion: Hyperactivity of hypothalamic-pituitary-adrenal axis causes elevation of glucocorticoid in the circulation that imparts deleterious influences on various systems, leading to brain damage and depression.
Keywords: prefrontal cortex